Effect of Circadian Rhythm Disturbance on the Human Musculoskeletal System and the Importance of Nutritional Strategies - Norsham Juliana; Liyana Azmi; Nadia Mohd Effendy; Nur Islami Mohd Fahmi Teng; Izuddin Fahmy Abu; Nur Nabilah Abu Bakar; Sahar Azmani; Noor Anisah Abu Yazit; Suhaini Kadiman; Srijit Das (MDPI AG, 2024)
Indexed by Scopus